Nutritional assessment of the most frequently consumed dishes in a slum in Iquitos, Peruvian Amazon - Guillermo Molina Recio; Rafael Moreno Rojas; María García Rodríguez; Manuel Vaquero Abellán (Nutrición Hospitalaria)
Introduction: Large nutritional surveys in Peru have identified the magnitude and location of the different types of malnutrition. The chronic type is the most prevalent one. However, although rates may be considered as alarming (even more in rural areas), only one of these studies contains information about intake characteristics, using 24-hour recalls (R24). That is, it lacks some other systems, adapted to the gastronomical characteristics of their regions and to the bioavailability of food in each area, in order to locate the origin of this situation and, thus, propose truly effective and efficient solutions. Aim: To determine the nutritional value of the main dishes consumed by the residents of a slum in Peruvian Amazon. Methods: Ninety-eight participants completed three 24-h recalls. Based on these data, we selected the 25 most commonly eaten dishes and evaluated their nutritional composition. We took note of the homemade recipes, weights and measures. In addition, we observed preparation and cooking. The mean nutritional composition of each dish was calculated per 100 g using the Nutriplato 4.6. software. We also calculated gains or losses resulting from culinary treatments. Results: Within those which include milk, the highest energy density is the mingado de arroz. In the group of fish, the most energetic is pescado frito, while within meat-based recipes tallarín con pollo, res asada and chancho frito are the most energetic ones. Regarding prepared dishes, the juane is the highest energy density of all recipes. Inside garnish, using bananas as the main ingredient, plátano frito and madurito are the most energetic. Fats are higher in fried dishes and those which contribute most fat ratio. The same thing happens with garnish as 100 grams of plátano frito or madurito contain more than 70% of the RDA. Res asada and juane present the highest sodium level. Conclusions: If we wish to offer healthier dishes, it is necessary to change their composition and/or cooking methods, reducing the consumption of fried foods. Sodium intake should also be reduced. Two foods could be important to that aim: menudencia de pollo, rich in B vitamins and low in fat, and frijol hervido, which is rich in vegetable protein and, with rice dishes ubiquitous in this area, increases the biological value of ingested proteins.